2021
DOI: 10.1021/acs.jnatprod.1c00087
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of 5-Methylpsilocybin: A Tryptamine with Potential Psychedelic Activity

Abstract: A novel analogue of psilocybin was produced by hybrid chemoenzymatic synthesis in sufficient quantity to enable bioassay. Utilizing purified 4-hydroxytryptamine kinase from Psilocybe cubensis, chemically synthesized 5-methylpsilocin (2) was enzymatically phosphorylated to provide 5-methylpsilocybin (1). The zwitterionic product was isolated from the enzymatic step with high purity utilizing a solvent−antisolvent precipitation approach. Subsequently, 1 was tested for psychedelic-like activity using the mouse he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…A pivotal report by Laatsch describes research to reveal structure-color correlations by analogously oxidizing specifically designed 4-hydroxyindole model compounds which carried specific methylations to interrupt product oligomerization at the dimeric level. [4] Inspired by this report, and supporting the recently accomplished chemoenzymatic synthesis of 5-methylpsilocybin, [7] we synthesized strategically 5-and 7methylated 1 derivatives that were oxidatively dimerized into stable compounds that could be isolated and characterized. To discern differences in oxidation and reaction behavior of hydroxylated tryptamines, the 5-hydroxy isomer of 1, bufotenin (3), was also chemically dimerized in a parallel approach and investigated for spectroscopic features.…”
Section: Introductionmentioning
confidence: 77%
“…A pivotal report by Laatsch describes research to reveal structure-color correlations by analogously oxidizing specifically designed 4-hydroxyindole model compounds which carried specific methylations to interrupt product oligomerization at the dimeric level. [4] Inspired by this report, and supporting the recently accomplished chemoenzymatic synthesis of 5-methylpsilocybin, [7] we synthesized strategically 5-and 7methylated 1 derivatives that were oxidatively dimerized into stable compounds that could be isolated and characterized. To discern differences in oxidation and reaction behavior of hydroxylated tryptamines, the 5-hydroxy isomer of 1, bufotenin (3), was also chemically dimerized in a parallel approach and investigated for spectroscopic features.…”
Section: Introductionmentioning
confidence: 77%
“…The 4-hydroxytryptamine kinase (PsiK) enzyme was purified from the Psilocybe cubensis fungus. On the basis of the amount of 561 isolated, the overall yield was 28% ( Figure 27 ) [ 100 ]. 5-Methyl-1 H -indol-4-ol ( 557 ) was acetylated with acetic anhydride and NaHCO 3 in toluene into compound 558 .…”
Section: Synthesis Of Indole Alkaloidsmentioning
confidence: 99%
“…It was then treated with oxalyl chloride, followed by dimethylamine in THF, to result in 559 , which, on reduction by LiAlH 4 , resulted in 560 . Compound 560 was incubated with PsiK and ATP for 16 h; the analysis of the mixture by HPLC indicated that 90% of it was successfully converted into 5-methylpsilocybin ( 561 ) with an overall isolated yield of only 40% [ 100 ].…”
Section: Synthesis Of Indole Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die meisten SARs zeigen, dass eine sterisch kleine Substitution in der C4-oder C5-Position des Indols toleriert wird. [26][27][28] Da aber keine der bislang untersuchten Substituenten in ihrer Größe mit einem Benzolring vergleichbar waren und noch keine dahingehenden SARs beschrieben waren, haben wir in unserem Ansatz auf die photophysikalischen Eigenschaften der Phenylazoindole fo-kussiert. Auch wenn Phenylazoindole noch keine Anwendung in der Photopharmakologie gefunden haben, wurden diese vielversprechenden Strukturen bereits ausführlich hinsichtlich ihrer photophysikalischen Eigenschaften charakterisiert.…”
unclassified